Unlocking Self-Esteem in Older Adults: A Conceptual Exploration of Technological Proficiency and Its Effects - Wenjie Zhu; Nurul Hidayu Mat Jusoh; Ribka Alan; Malisah Latip; Juniza Md Saad (Behavioral Sciences)
With the current rapid increase in digital technology adoption, understanding the relationship between technological proficiency and self-esteem is crucial to older adults. This study explores the mechanisms through which technological proficiency influences self-esteem, particularly considering its associations with technological engagement, self-efficacy, social participation, and autonomy. By using a narrative review approach, this study synthesizes recent findings from gerontology and psychology to examine these relationships. The analysis shows that higher technological proficiency enhances self-esteem by boosting self-efficacy, fostering social participation, and promoting greater autonomy. Older adults who are skilled in using digital tools exhibit greater confidence in managing daily activities and maintaining their social networks, contributing to their psychological resilience. Conversely, lower technological proficiency is linked to frustration, social exclusion, and diminished self-esteem, exacerbated by the digital divide. However, despite these insights, much remains unexplored; for example, no longitudinal study has been conducted to capture the dynamic relations between technological proficiency and self-esteem. These findings suggest that further research is needed to learn more about how technological proficiency influences self-esteem and recommend clinical ways of supporting older adults in their current stage.